2021
DOI: 10.1021/acs.jafc.1c00205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Reduced IgG/IgE Binding Abilities of Glycated β-Lactoglobulin and Its Digests through High-Resolution Mass Spectrometry

Abstract: Glycation between proteins and reducing sugars is the common chemical modification in food protein, and many studies have focused on the allergenicity of the glycated protein. However, a systemic study on the allergenicity change of its digests is lacking. In this work, we explored the change rule of the digestibility and allergenicity of glycated β-Lg during in vitro gastrointestinal digestion and interpreted the mechanism using high-resolution mass spectrometry. Glycation with arabinose increased the resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…After pepsin digestion, MS/MS with HCD was performed to identify the glycated peptides. In theory, if a peptide is covalently bound with one d -galactose molecule, the corresponding m / z peak of the peptides will increase to 162, 81, and 54 at charges of +1, + 2, and +3 after losing a molecule of water . Similarly, when a peptide is covalently bound with two molecules of d -galactose, the m / z peak of the peptide could be 324 Da.…”
Section: Resultsmentioning
confidence: 99%
“…After pepsin digestion, MS/MS with HCD was performed to identify the glycated peptides. In theory, if a peptide is covalently bound with one d -galactose molecule, the corresponding m / z peak of the peptides will increase to 162, 81, and 54 at charges of +1, + 2, and +3 after losing a molecule of water . Similarly, when a peptide is covalently bound with two molecules of d -galactose, the m / z peak of the peptide could be 324 Da.…”
Section: Resultsmentioning
confidence: 99%
“…However, our literature review showed that the possibility of glycation reducing the IgE binding capacity of β-lactoglobulin compared with the heating process seems to be related to the sugar type, reaction condition, and detection sera used. For example, when ribose, fructose, maltose, or arabinose was present, glycation further reduced the IgE binding capacity of β-lactoglobulin compared to heating, but reaction with lactose did not cause much difference because lactose induced a much lower glycation degree, and those glycated sites were not on main epitopes [ 29 , 30 ]. Under some dry and wet heating conditions, individual difference in the sera used even determines the increase or decrease in the IgE binding capacity [ 31 ]; see Table 1 for more detailed reaction conditions.…”
Section: Maillard Reaction and Allergenicity Of Foodsmentioning
confidence: 99%
“…The IgG binding rate was markedly influenced by high temperatures and long periods of treatments, with a maximum decline to 28% when treated at 200 °C for 10 min. The reduction in the IgG-binding ability of OVM may be due to the structural changes derived from amino acid modification and denaturation [ 15 ]. The results implied that SS-created extreme high temperatures of up to 200 °C might influence the protein structure and destroy IgG allergenicity epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…SS treatment, particularly at high temperatures and long processing times, could induce the OVM aggregation, increase surface hydrophobicity, modify the functional groups and amino acids in OVM. These phenomena disrupted and buried some allergen epitopes and made it difficult for the combination of antibodies and antigens [ 14 , 15 ]. Therefore, the allergenicity of OVM was decreased and the anaphylactic reaction in the KU812 cell was inhibited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation